Analisis Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Apoteker di Klinik-Klinik Pratama Kota Pekanbaru: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA APOTEKER DI KLINIK-KLINIK PRATAMA KOTA PEKANBARU - Erniza Pratiwi (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2020)
Every employee in a company needs to get satisfaction at work which can also have an impact on improving employee performance. Job satisfaction is an attitude in the form of a reflection of the employee's feelings towards the whole job which consists of various aspects. Someone who is satisfied in their work will have high motivation, commitment to the organization and work participation so that they will continue to improve their performance. The purpose of this study was to find out what are the factors that influence the job satisfaction of pharmacists in the clinics of pratama of Pekanbaru. This study is a descriptive analytic study with a cross-sectional study design using a job satisfaction questionnaire. The sample in this study was a pharmacist who worked in the pratama clinics totaling 55 people taken by simple random sampling technique. The results obtained showed that the most dominant factors affecting the pharmacist's job satisfaction in the clinics of Pratama Kota Pekanbaru were job security (78.91%), fair treatment (78.84%), relationships between colleagues (78.04%) , salary and promotion (77.30%), working conditions (77.16%) and relationship with the leader (76.00%).